KOMUNIKASI TERAPEUTIK ANTAR TERAPIS DAN PASIEN KOMUNITAS TOTOK PUNGGUNG INDONESIA DAERAH SUMBAWA - Azzubair, Muhammad Itsar; Anshori, Muhammad Syukron (Jurnal Common, 2021)
This study was presented to find out how therapeutic communication activities between therapists and patients in the Indonesian Accupreasure Community in the Sumbawa area. The theory used is the theory of therapeutic communication according to Stuart, G.W., and Sundeen about the four phases of therapeutic communication, therapeutic communication techniques, and Egan's theory of therapeutic communication attitudes. This study is a qualitative descriptive study, whose data collection uses non-participant observation techniques, unstructured interviews, and documentation. In this study, informants were selected based on purposive sampling. Data analysis will go through the stages of data collection, data presentation, data reduction, and conclusions. The results obtained in the study through four phases of therapeutic communication among others: 1. In the pre-interaction phase in which therapists are concerned about everything that will be related to the practice process both patient and mental data from the therapist itself. 2. The orientation phase is used by the therapist as the first step in fostering a trusting relationship before giving the first diagnosis. 3. The working phase is that the therapist builds positive dialogue during the process of muscling. 4. Evaluation phase, continued communication between the therapist and the patient after getting the therapy action. Therapeutic communication is planned and professional communication, so it is important for the therapist to actively coordinate and harmonize the communication relationship between the therapist and the patient.